Design, synthesis and in vitro activity of phidianidine B derivatives as novel PTP1B inhibitors with specific selectivity. Issue 3 (1st February 2016) - Zhang, Li; Jiang, Cheng-Shi; Gao, Li-Xin; Gong, Jing-Xu; Wang, Zhong-Hua; Li, Jing-Ya; Li, Jia; Li, Xu-Wen; Guo, Yue-Wei
Graphical abstract: Function-oriented synthesis of phidianidine B derivatives was accomplished, their specific inhibitory effects on PTP1B, the SAR and molecular docking analysis were described. Abstract: A series of phidianidine B derivatives were synthesized by introducing various heterocyclic rings. Their inhibitory effects on PTP1B and other PTPs (TCPTP, SHP1, SHP2 and LAR) were evaluated. A majority of them displayed significant inhibitory potency and specific selectivity over PTP1B. The SAR and molecular docking analysis were also described.